Asociaciones de larvas de peces en una bahía del Caribe mexicano - Quintal-Lizama, C (2001)
Interannual ichthyoplankton variation, was analyzed in Bahía de la Ascensión, Mexico, during December of four consecutive years (1994-1997). A total of 32 families, 35 genera and 21 species of fish larvae were identified. The most abundant fish larvae were the Gobiidae followed by the Callionymidae, Clupeidae and Tetraodontidae. Larval diversity was low when compared with other periods (“dry” and “rainy”). Three spatial associations (internal, medium and external) were found in December 1994 and 1995. In 1996-1997, stations of the inner and outer parts of the bay were mixed. The dominant families characterized most of the faunal associations. Egg density was highest in the external zone of the bay, whereas larvae were most abundant in the inner area. Major factors affecting the fish larval assemblages during December (1994-1997) in Bahía de la Ascensión seem to be related to the nursery areas location and to the tropical fishes reproductive period.